2011
DOI: 10.1007/s00198-011-1742-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparable outcomes in fracture reduction and bone properties with RANKL inhibition and alendronate treatment in a mouse model of osteogenesis imperfecta

Abstract: We report a direct comparison of RANKL inhibition (RANK-Fc) with bisphosphonate treatment (ALN) from infancy through early adulthood in a mouse model of Osteogenesis Imperfecta. Both ALN and RANK-Fc decreased fracture incidence to the same degree with increases in metaphyseal bone volume via increased number of thinner trabeculae. The potential therapeutic benefit of RANKL inhibitors in OI is under investigation. We report a direct comparison of RANKL inhibition (RANK-Fc) with bisphosphonate treatment (alendro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 46 publications
5
47
0
Order By: Relevance
“…Treatment ended 12 weeks after the transition time point. Doses of RANK-Fc and ALN were based on results of previous studies that showed increased bone mineral density without side effects using the same dose [1][2][3]. Weaning was carried out between 3 and 4 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment ended 12 weeks after the transition time point. Doses of RANK-Fc and ALN were based on results of previous studies that showed increased bone mineral density without side effects using the same dose [1][2][3]. Weaning was carried out between 3 and 4 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Our group has used the oim/oim mouse model as an analog for evaluating pharmaceutical therapies for moderate-to-severe OI [1-3, 9, 13, 27-29]. The oim/oim mice, as a result of an inappropriate stop codon in the collagen I alpha 2 chain's gene, have a aI(I) 3 triple helix instead of the expected aI(1) 2 aI(2) helix [11] and provide a reproducible model with a moderate-to-severe (Type III) form of OI [34], including the presence of spontaneous fractures. Both alendronate (a bisphosphonate) and RANKFc, an inhibitory antibody to RANKL (receptor activator of nuclear factor-jB ligand), tested in short-term (8-week) studies showed a comparable reduction in the number of fractures relative to saline-treated oim/oim mice [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the bone structural parameters, cyclicCHAD was especially effective in preserving the trabecular number. This effect could be explained by the preferential remove of the thinnest trabeculae (PRETT) mechanism, (37,38) that relies on the fact that the thinnest metaphyseal trabeculae, which play a prominent metabolic role, are more prone to be resorbed by osteoclasts and have a shorter lifetime. Therefore, blocking osteoclast bone resorption prevents their disappearance and, as a consequence, their number is higher than in vehicle-treated animals.…”
Section: Discussionmentioning
confidence: 99%
“…In preclinical study, Raggio and colleagues found that BPs and RANK-FC could decrease fractures in the mouse model of OI. (2,3) In OI patients, however, the effects of BPs on the fracture reduction in several randomized control trials are still inconsistent. (4,5) The second issue raised by Raggio and colleagues was that we compared the treatment effect of strontium ranelate on fracture reduction to the brtl/þ mice but not to the results that they reported.…”
mentioning
confidence: 99%